Kebangkitan Agama Buddha Pascakemerdekaan Indonesia: Studi Historis dan Kultural Vihara Buddhagaya Watugong - Joko Adi Pradana (Jurnal Budi Pekerti Agama Buddha, 2025)
This study explores the role of Vihara Buddhagaya Watugong as a center for the revival of Buddhism in post-independence Indonesia. The main objective is to understand how this vihara contributed to the revitalization of Buddhism through historical, cultural, and spiritual lenses. A qualitative descriptive approach was employed, involving archival research, in-depth interviews, architectural observation, and oral history. Findings reveal that Vihara Buddhagaya Watugong serves multiple functions as a place of worship, cultural hub, and interfaith dialogue platform. Its architectural features, such as the Avalokitesvara Pagoda and other sacred elements, illustrate a fusion of Buddhist values and local wisdom. The vihara actively engages in education, tradition preservation, and the strengthening of Buddhist religious identity within a multicultural society. These results suggest that the revival of Buddhism in Indonesia is not solely a spiritual phenomenon but also contributes to the national narrative of cultural identity and social harmony. Thus, Vihara Buddhagaya Watugong stands as a significant symbol of religious revitalization, cultural heritage, and social cohesion in modern Indonesia.